Dapagliflozin Improves Endothelial Integrity And Cardiac Loading Through A Sphingosine-1-phosphate / Apolipoprotein M Dependent Pathway - Ripoll, Carla Valenzuela; Guo, Zhen; Kumari, Tripti; Girardi, Amanda; Diab, Ahmed; Özcan, Mualla; He, Li; Oscarsson, Jan; Esterline, Russell; Schilling, Joel; Kosiborod, Mikhail; Cho, Jaehyung; et al. (Journal of cardiac failure, 2022)
Sodium-glucose co-transporter 2 inhibitors (SGLT2i) reduce hospitalization and mortality in chronic heart failure and kidney disease, and are actively being tested in acute settings. Recent pre-clinical studies suggest that SGLT2i improve survival and renal inflammation acutely after lipopolysaccharide (LPS) administration, but just as in the chronic setting, the downstream beneficial effects of SGLT2i remain elusive. In response to cardiometabolic disease or inflammation, humans and mice downregulate the apolipoprotein M (ApoM) / sphingosine-1-phosphate (S1P) pathway, leading to increased death and organ injury. Because of the phenotypic similarities between SGLT2 inhibition and the ApoM/S1P pathway, we hypothesized that the SGLT2i dapagliflozin (Dapa) improves cardiorenal outcomes in a murine LPS model via an ApoM/S1P dependent pathway. Diet-induced obesity mice were randomized to Dapa (1 mg/kg PO) or vehicle for 4 days, followed by saline or LPS (10 mg/kg IP), echocardiography, and euthanasia. To assess if Dapa attenuates vascular permeability and neutrophil transendothelial migration, intravital microscopy (IVM) was performed in chow-fed Ly6g-cre Tdtomato mice, ApoM transgenic (ApomTG) mice, and littermate controls. Dapa attenuated LPS-induced reductions in cardiac index (-3% with Dapa vs -48% in controls, p<0.01), end-diastolic volume index (+28% with Dapa vs -34% in controls, p<0.01), coronary sinus area (+27% with Dapa vs -75% in controls, p<0.05), and serum ApoM (-5% with Dapa vs -60% in controls, p<0.01). IVM demonstrated that Dapa reduced vascular leak and neutrophil transendothelial migration. ApomTG mice demonstrated reduced vascular leak, but were insensitive to Dapa, while treatment of mice with an S1P receptor inhibitor blocked the effects of Dapa on vascular leak. The effects of SGLT2i on endothelial integrity and cardiac function are clinically relevant to conditions such as sepsis and heart failure, among others, and merit further clinical investigation. ApoM/S1P signaling is a critical downstream link that mediates the beneficial effects of Dapa on endothelial barrier integrity.